Multiple Histories and diversity in African metallurgies - (:unkn) unknown (My University, 2018)
To write a history of the processes and techniques involved in metallurgy in Africa, one expects to start at the beginning. Alas, this initial period of elaboration remains an enigma in regards to time (when does metallurgy appear in Africa?), conduct (what metals were first produced and what processes were employed?), and development (how do metallurgical practices diffuse?). The answers to this enigma have been a point of contention and debate for more than a century, a debate which has been amplified over the years and thus only aggravated the diversity in points of view. The true underlying question in the conflict is critical (and can often take some rather polemic turns): is Africa another cradle development of metallurgy or not? Were these techniques developed independently by Africans or introduced from other regions? Moving beyond these elements of debate, for which it is important to comprehend what data and what criticisms are involved, in this communication we will attempt to demonstrate that the originality of the African continent does not reside uniquely in the precocious nature of metallurgical techniques – a point that remains unsettled –, but rather in the plurality of regional, perhaps even local, historical trajectories that associate autonomous technical developments with the large scale circulation of materials and finished objects. Understanding the singularity of African societies in this respect remains a significant challenge to research. For this reason we will finish our presentation with the questions that palaeometallurgy can answer by enumerating the archaeological remains required and the analytical tools that can be employed.
Keywords: African Research